Teoría de la formación categorial : ruta de análisis didáctico para la educación física (2005)
ABSTRACT: The text contains conceptual foundations frorn the theory of categorial formation that allow to direct corporal education. It is based on the anthropoIogical ped agogical assumption that the human being is a Iacking unfinished and helpIess being needing education, but with the strength that leads him to selfconstruction. The theory of categorial formation, stemming from Derbolav and Klafki, offers a didactic path to make inferences as to when certain content (Inhalt) has formative content (Cehalt); in it we find a hermeneutic foundation that poses as central axis the extraction of the meaning of the contents being taught in light of the farmative aspect, of its reason why, and of its aim (telos)